Depressive Symptoms and Violence Exposure: Contributors to Repeat Pregnancies Among Adolescents - Anderson, Cheryl A. (J Perinat Educ, 2015)
Depressive symptoms and violence exposure (VE) often cooccur and have been recognized to influence childbearing; contribution to repeat pregnancy is unclear and examined in this article. This cross-sectional, descriptive, study screened for depressive symptoms and VE among 193 adolescent mothers at a large county hospital in Southwestern United States. Repeat pregnancy and depressive symptoms characterized one-third and one-quarter of adolescents, respectively. Despite minimal disclosure of VE, repeat pregnancy was significantly influenced by child abuse and past traumatic life experiences. Assessments and interventions with adolescents should focus on frequency of repeat pregnancies and symptoms of depression and VE. Nurses and childbirth educators are poised to offer birth control information and education, support, and resources highlighting depression and VE to adolescents.